PENGEMBANGAN MODEL PEMBELAJARAN VOLI FOREHAND TENIS LAPANGAN - Ade Ros Riza (Jurnal Pedagogik Olahraga, 2015)
In general, the purpose of this research and development was to produce a learning model of serve tennis on PJKR Student’s Facullity Sport of Science. The development research was user a model of Research & Development (R & D) approach of Brog and Gall. The subjects of the research and development were 38 PJKR Student’s Facullity Sport of Science Unimed, North Sumatera. In testing the effectiveness of the development of this serve tennis learning model can be seen from the psychomotor data and result of serve. The effectiveness level of the previos teaching model was 66% of the expected criteria.The effectiveness level of a new learning model is was 96% of the expected criteria, it meant that there was an increase of 30%. Based on this research, it can be concludedthat: (1) learning model of serve tennis canimprove tecknik of serveand result of serve, (2) the learning model was more effective and efficient in order to increase students interestand motivation inlearning physical education. Keywords : Model Of Learning, Volly Tennis